Auditory and kinaesthetic learning styles and L2 achievement: A correlational study - Masela, Maximeliana; Subekti, Adaninggar Septi (Englisia: Journal of Language, Education, and Humanities, 2021)
This study investigated undergraduate non-English major university students’ auditory and kinaesthetic learning styles and their relationships to second language (L2) achievement in English. It was conducted to resolve the conflicting findings in the literature on the directions and strength of the relationships between learners’ learning styles and their achievements and to investigate the field in relatively under-researched Indonesian participants. The study used a survey as the method of data collection and found out that learners used auditory slightly more dominantly from kinaesthetic, yet both learning styles were merely used at low to moderate levels. The study further found very weak and statistically not significant associations between these learning styles and L2 achievements, suggesting that contrary to various learning theories highlighting the importance of learners’ learning styles in L2 learning, these learning styles may not be an important determinant of L2 achievement. Based on the findings, possible future studies are suggested concerning the implications, contributions, and limitations of the study.